Boosting power conversion efficiency by hybrid triboelectric nanogenerator/silicon tandem solar cell toward rain energy harvesting. (April 2021) - Zhao, Leilei; Duan, Jialong; Liu, Liqiang; Wang, Jianwei; Duan, Yanyan; Vaillant-Roca, L.; Yang, Xiya; Tang, Qunwei
Abstract: The weather-dependence and intermittent photoelectric conversion capacity of the traditional photovoltaics call for rational design on device architecture to realize persistent power output under multiple-energy-source stimuli. Herein, we demonstrate a novel triboelectric nanogenerator/silicon (TENG/Si) tandem hybrid solar cell by stacking top silver/polydimethylsiloxane sub-cell onto bottom monocrystalline Si solar cell for simultaneously harvesting solar and rain energies. Upon systematically optimizing the device configuration and the properties of top nanogenerator, the bottom Si solar cell is used as a friction layer to regulate the charge distribution of TENG, achieving a short-circuit current of 7.59 μA, a peak open-circuit voltage of 37.19 V under the stimuli of single raindrop and a power conversion efficiency enhancement by 20% in comparison with pristine Si solar cell. Finally, 26 blue light-emitting diodes can be lighted up by one raindrop. Given the compelling advantages of enhanced power output and expanded working time, this physical proof-of-concept TENG/Si tandem hybrid solar cell provides new opportunities to collect multiple energies from nature and to promote the development of weather-independent solar cells. Graphical Abstract: A nanogenerator/silicon tandem solar cell to simultaneously harvest solar energy and rain energy has been fabricated by a new proposed two-electrode mode triboelectric nanogenerator, in which the whole Si solar cell plays a role of friction layer. Arising from the regulated charge distribution, the total power generation is enhanced by 20% in comparison with pristine Si solar cell in sunny days. ga1 Highlights: Nanogenerator/silicon tandem solar cells are prepared to harvest rain and solar energies. The top nanogenerator presents a two-electrode by sharing a Al electrode with Si slice. The tandem solar cell achieves an I SC of 7.59 µA and a V OC of 37.19 V in stimuli to a raindrop. 26 blue LEDs can be lighted up by one raindrop. The total power generation is enhanced by 20% in comparison with pristine Si solar cell.